Improving Calculus II and III Through the Redistribution of Topics. Issue 3 (3rd April 2016) - George, C. Yousuf; Koetz, Matt; Lewis, Heather A.
Abstract: Three years ago our mathematics department rearranged the topics in second and third semester calculus, moving multivariable calculus to the second semester and series to the third semester. This paper describes the new arrangement of topics, and how it could be adapted to calculus curricula at different schools. It also explains the benefits we have seen both for our math majors and for majors in other departments, and how we have dealt with the challenges that we have encountered.